Validity and Reliability of the Urdu Version of the McLean Screening Instrument for Borderline Personality Disorder - Munawar, Khadeeja; Aqeel, Muhammad; Rehna, Tasnim; Shuja, Kanwar Hamza; Bakrin, Faizah Safina; Choudhry, Fahad Riaz (Frontiers in Psychology, 2021)
Introduction: Although the translation and validation of the McLean Screening Instrument for Borderline Personality Disorder (MSI-BPD) are performed in various languages and samples, no study has established the validity and reliability of the Urdu version of MSI-BPD in individuals with cardiac problems. Materials and Methods: The Urdu version of the MSI-BPD was prepared through the standard back-translation method. The translation and adaption were completed in four steps: forward translation, adaption, and translation, back translation and committee approach, and cross-language validation. The sample, selected through the purposive sampling method, comprised of 150 adults with cardiac problems (males = 75 and females = 75), with an age range of 23-78 years (M = 55, S.D. = 10.6). The Cronbach alpha reliability and factorial validity of the MSI-BPD were assessed through confirmatory factor analysis (CFA) and Pearson correlation analyses. Internal Consistency and test-retest reliability (at 2 weeks' interval) were used to evaluate the reliability. Statistical analyses were performed using SPSS (version 22) and Structural Equation Modeling (SEM) software. Results: Preliminary analysis revealed that the overall instrument had good internal consistency (Urdu MSI-BPD α = .79; English MSI-BPD α = .77) as well as test-retest correlation coefficients over a period of 15 days (r = .94). Conclusions: Findings suggested that the MSI-BPD, with important limitations, can be used as an effective preliminary screening tool to measure BPD in Urdu-speaking adults with cardiac problems. Further validations should be conducted to make the translated version of the MSI-BPD an appropriate tool to screen BPD in hospitals and mental health care settings.